Design‐led Innovation Readiness: priming micro SMEs for strategic innovation - Bailey, Mark; Spencer, Nicholas; Carrion‐Weiss, Justine; Arakelyan, Arman; Carter, Anthonia (Design Management Journal, 2022)
This research explores innovation‐readiness in the context of design‐led innovation in micro, small and medium‐sized enterprises (MSMEs). It builds on work undertaken and published by the lead author's team in 2018. This reported on the team's rapid design‐led intervention for supporting organisations to establish innovation readiness. Since it first delivery, the approach has been deployed with over 60 separate enterprises across three different countries; UK, USA, and Armenia. It has evolved to be delivered through different modes; one‐to‐one, one‐to‐many, face‐to‐face and on‐line. Further, it has been developed in such a way that postgraduate students, or ‘novice facilitators’, can take an active role in its delivery. Facilitation teams have invariably included at least one facilitator with a design background. Participants were enterprise founders or leaders. In this study a mixed‐methods approach is used, combining thematic analysis of participant surveys, co‐reflection and semi‐structured interviews with participants and facilitators. Findings suggest that this design‐led approach delivers different benefits from typical business innovation readiness assessment and audit tools. It involves a form of co‐creative, speculative knowledge venturing that supports enterprises in not only understanding their innovation readiness, but also in creating and mapping strategic innovation opportunities, thereby priming them to engage in design‐led innovation practices. This co‐creation of knowledge leads to both new knowledge about the innovation readiness of the enterprise and new innovation opportunities. It is revealed as a fundamental, catalytic aspect of the programme irrespective of mode, or location, of delivery. This paper will be of interest to researchers and practitioners who are seeking to develop innovation support programmes working with SMEs and MSMEs.